1996
DOI: 10.1016/s1071-5576(96)00043-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of creatine kinase isoenzymes in human placenta during early, mid-, and late gestation

Abstract: Expression of uMtCK and BCK in human placenta is highly regulated, and post-transcriptional regulation of uMtCK and BCK expression occurs in the term placenta. The coordinate regulation of uMtCK and BCK in human placenta supports the CP shuttle hypothesis. This analysis demonstrates that human placenta has high energy needs that can change rapidly; thus, a functioning CP shuttle may be important in the maintenance and termination of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…We confirmed the decrease in creatine phosphate by showing a significant reduction in CK activity in term samples. Our findings complement the data of Thomure et al (1996 ) who found reduced ubiquitous mitochondrial and cytosolic brain CK protein expression in term samples, compared with first and second trimester placentas. We also describe a remarkable increase in the PDE spectral intensity fraction and the PDE/PME spectral intensity ratio towards term.…”
Section: Discussionsupporting
confidence: 90%
“…We confirmed the decrease in creatine phosphate by showing a significant reduction in CK activity in term samples. Our findings complement the data of Thomure et al (1996 ) who found reduced ubiquitous mitochondrial and cytosolic brain CK protein expression in term samples, compared with first and second trimester placentas. We also describe a remarkable increase in the PDE spectral intensity fraction and the PDE/PME spectral intensity ratio towards term.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to the brain, the amount of TCr measured in the placenta of the spiny mouse increased significantly with advancing pregnancy. Being metabolically very active, it is likely that the placenta itself has a requirement for creatine – creatine kinase expression, which is tightly coupled with cellular energy requirements, peaks in term human placenta [ 39 ]. However, as for the human placenta [ 4 ], it appears that this organ itself does not synthesize creatine, as we were unable to detect either AGAT or GAMT mRNA or protein in the placenta of the spiny mouse from mid-gestation to term.…”
Section: Discussionmentioning
confidence: 99%
“…Cr is thought to be actively transported across the placenta from maternal circulation during pregnancy, with placental Cr transporter expression evident as early as 13 weeks of gestation [ 62 ]. Expression of mitochondrial and cytosolic CK enzymes in the placenta is highly coordinated and markedly increased in the third trimester, concomitant with increased metabolic activity of the placenta in late pregnancy [ 63 ]. It remains unclear when the human fetal reno-hepatic axis for endogenous Cr synthesis is established, although studies in the precocial spiny mouse indicate that this axis develops late in gestation [ 64 ].…”
Section: Creatine and Perinatal Hypoxic Ischemic Injurymentioning
confidence: 99%